Developing Comprehensive Sexuality Education in Primary English Teacher Instruction via Picturebooks - Beacon, Griselda (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper focuses on how mediation around contemporary children’s picturebooks contributes to developing Comprehensive Sexuality Education (CSE) in primary English teacher instruction. It discusses picturebooks from a gender perspective, introduces queer pedagogy to articulate with gender and sexual diversity and elaborates upon creative teaching ideas with a focus on language learning, art and critical thinking on identity construction.